Pengaruh Penengendalian Internal, Budaya Organisasi Dan Kompetensi Terhadap Kinerja Keuangan Lembaga Perkreditan Desa (LPD) Se-Kecamatan Tampaksiring - Ni Kadek Desi Dwipayani; I Wayan Sudiana; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2026)
This study aims to analyze the influence of internal control, organizational culture, and competence on the financial performance of Village Credit Institutions (LPD) throughout Tampaksiring District. This type of research is quantitative using a survey method by distributing questionnaires to 177 respondents who are LPD administrators and employees. Data were analyzed using multiple linear regression analysis techniques. The test results show that organizational culture and competence have a positive and significant effect on financial performance, while internal control does not have a significant effect. These results indicate that improving a strong organizational culture and good individual competence play an important role in supporting LPD financial performance. Conversely, the implementation of suboptimal internal control causes ineffectiveness in improving financial performance. Therefore, the main focus in the development of LPD in the future needs to be directed at improving HR competence and strengthening organizational culture that supports integrity, transparency, and collaboration.